Positive Peer Reporting for Middle School Students With Emotional and Behavioral Disorders. (March 2023) - Haydon, Todd; Kennedy, Alana; Murphy, Meredith; Boone, Jason
Students with disruptive behavior problems can contribute to loss of instruction time in the classroom and may cause irritation for peers. However, peers can serve as powerful change agents in the classroom. Promoting positive peer interactions is especially important for students with emotional and behavioral disorder (EBD). One effective approach to promote prosocial behaviors and support students with EBD is positive peer reporting. The use of positive peer reporting decreases negative interactions among peers by increasing prosocial behaviors. This column reviews the literature about this strategy, discusses the ways in which it can be adapted to best fit the needs of students, and provides guidance and recommendations for how to implement these approaches in an applied setting.